peningkatan hasil belajar ilmu pengetahuan alam materi posisi dan bayangan matahari siswa kelas II melalui model pembelajaran kooperatif tipe picture and picture di SDN Tanjung Barat 09 Tahun pelajaran 2017-2018 - Marthazilla Febby Ahmad; Ni’mah Fauziah; Okta Rosfiani; Saskia Rachman (Madako Elementary School, 2024)
Science learning will always be relevant in developing students' science concepts that are measurable from the achievement of learning outcomes. The purpose of this study, designed with the classroom action research method, was to find out whether students' concepts of position and sun shadow material science improved by applying a picture and picture type cooperative learning model based on test analysis, documentation, observation, and field notes. Teachers and 26 grade II students of SDN Tanjung Barat 09 were involved in the research. The results of this study showed that the classical completeness of student learning outcomes became better from pre-cycle (42.30%), cycle-I (65.40%) to cycle-II (80.80%). This means that the application of the applied learning model helps students gain knowledge and understanding of science about the position and shadow material of the sun, which is part of the science material available in elementary schools. The contribution of the results then recommends teachers to maximize the application of the teaching model in strengthening students' understanding of science concepts regarding teaching material juxtaposed with the implementation of the model studied.